(3MOGFb GdCRgGQ aj TQM eTGQb GdCfhGQs - (3hLg GdOjf YeQ Hf YHO GdeMSf GdCQR fLGfis; (3QVj GdOjf CHj GdaVGFd GdMSf Hf eMeO CHh GdMSf, MjOQ GdUGZGfj,J (B650 (3g` ? s ((3bdjM Hf eMeO Hf Ydi GdNhGQRei s)
(3ChdgG (B:s
(3bGd GdEeGe GdGQRfLGfi CMeO Gddg Ydi JhGJQ aVdg Md eTcdGJ cJGH eTGQb GdCfhGQ GdfHhjI bGd GdUfYGfi GddGe ai GdMeO dJYQja GdLfS heYfGg GdETGQI s
(3BNQgG (B:s
(3hEf CNQJ LGR dGf GdhGh ddLeY GdeWdb hGddg GYde HGdUhGH Je GdcJGH HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B214s
Keywords: (3GdMOjK h GdeUWdMs